Quantitative Assessment of Baseline Serum HDL-C to Predict Gout Flares During Urate-Lowering Therapy Initiation: A Prospective Cohort Study [Corrigendum] - Jiang C; Li M; Chen Y; He Y; Li X; Cui L; Qi H; Cheng Z; Zhang X; Li C; Lu J (Journal of Inflammation Research)
Jiang C, Li M, Chen Y, et al. J Inflamm Res. 2024;17:11235–11245. The authors have advised there is an error in the author list on page 11235. The first affiliation should be “Shandong Provincial Clinical Research Center for Immune Diseases and Gout, The Affiliated Hospital of Qingdao University, Qingdao, People’s Republic of China”. The authors apologize for this error.